Hydrogen Generator Design Using Motorcycle Electricity Source - Jalu Nur Septiyanto (Institut Teknologi Adhi Tama Surabaya, 2025)
The global energy crisis has led to a spike in crude oil prices that has had a significant impact on the world economy. Indonesia, as a country facing a real energy crisis, is experiencing increasing energy consumption and decreasing availability of primary fossil energy. To overcome this problem, people are expected to save fuel by reducing the use of private vehicles. This research aims to develop a hydrogen generator model that uses electricity from motorbikes as an effort to save fuel. The hydrogen generator is designed with several sample models, the first using 4 stainless steel plates, the second 8 stainless steel plates and the third 12 stainless steel plates by connecting two electrolytic cells in parallel. In the experiments, the number of stainless steel anode and cathode plates was varied and the voltage was set at 12 voltages and 6 amperes of current, and tested using 2 methods, namely water and water with baking soda to evaluate the effect on hydrogen production. The results showed a certain trend in hydrogen production related to the variation of the parameters tested and the most effective in this test is 4 plates of water (800 ml) with 10 grams of baking soda and 8 plates of water (800 ml) with 10 grams of baking soda on the manometer gauge an increase of 1 ml.